Comparison of LMSs: Which is the Most Suitable LMS for my Needs? - Caminero, Agustin C; Hernandez, Roberto; Ros, Salvador; Tobarra, Llanos; Robles-Gomez, Antonio; Pastor, Rafael (International Journal of Emerging Technologies in Learning (iJET), 2013)
The role of Learning Management Systems (LMSs) is very important when conducting educational activities, spe- cially in the case of distant education â?? when its use becomes essential since all the interactions among the participants in the learning/teaching process are conducted though it. There are a number tools to provide this functionality, both open-source (such as .LRN, Sakai, or Moodle) and proprietary solutions (such as Blackboard). Given the wide variety of existing LMSs, it is worthwhile to devote effort in order to figure out which LMS is the most suitable for my needs? This paper strives at answering this question by presenting a twofold evaluation that compares three of the most widely used open-source LMS, namely .LRN, Sakai, and Moodle. First, a performance evaluation is presented that shows the different levels of use of the hardware resources (e.g. CPU, memory, I/O) of the machine the LMS is running on. Second, a performance evaluation from the point of view of the system administrators is also presented.